The NLQF : driving the convergence of the formal and non-formal education sectors - Jansen, Frederike G. S. [Verfasser]; Pijls, Tijs [Verfasser]; Smit-Toet, Hanneke [Verfasser] (My University, 2025)
„The Netherlands Qualifications Framework (NLQF) was established in 2011 as the national adoption of the European Qualifications Framework (EQF) and was enshrined in law in January 2025. This article explores the impact of the NLQF in enhancing the transparency, standardisation and governance of qualifications in the formal and non-formal education sectors, for lifelong learning initiatives, and how its future potential within the evolving educational landscape can be assessed.“ (authors‘ abstract; BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.2.1 Westeuropa; G 1.2.3 Qualifikationsentwicklungen; 370; Nationaler Qualifikationsrahmen; Niederlande; Qualifikationsnachweis; Lernergebnisorientierung; Nicht-formale Qualifikation; Transparenz; Zukunftsperspektive